Sequence stratigraphic framework for top seal development: examples from the Skull Creek and Graneros shales, Denver basin - Edwards, Kimberly, K., author; Sutton, Sally J., advisor; Ethridge, Frank G., advisor; Almon, William R., committee member (Colorado State University. Libraries, 1999)
In general, the distal open marine shelf setting, typified by the Graneros Shale produces a rock with a greater and more uniform seal capacity relative to the rocks of a proximal open marine shelf setting, such as those of the Skull Creek Shale. A distal setting, which usually corresponds to the time of maximum transgression, may produce better seals because there is less coarse clastic sediment input, which allows slow deposition of clays from suspension to be the dominant depositional process. In this study, the higher capacity seal rocks occur in the upper parts of the TST, either within the condensed section or below it. The Skull Creek locations show seal occurrence to be stratigraphically higher on depositional topographic highs, and lower in areas that were topographically low at the time of deposition. Top seal capacity was quantified with mercury injection capillary pressure (MICP) analysis. Other physical characteristics of these marine shales were studied but only porosity, permeability, total clay, and hydrogen index consistently demonstrated a significant correlation with seal capacity in both units. Shales that are well laminated with a high percentage of total clay and/or total organic carbon with a type I-II (marine) kerogen may or may not qualify as the best seal. Top seal capacity may be more a function of rock fabric rather than mineralogy. For example, two samples may have exactly the same amount of quartz, as shown by XRD analysis, but thin section examination reveals that the majority of quartz in one sample is present as grains and in the other sample as cement. Samples with cement usually provide a better seal because they decrease the pore throat diameter, thus increasing the amount of hydrocarbons that can be trapped. Seal quality in both the Skull Creek and Graneros Shales is quite variable throughout each of the facies within the TST deposits.
Covers not scanned.
Keywords: Denver Basin; Shale; Geology, Stratigraphic